Source Identification Performance of Plastic Scintillator Ranging from 100–1300 keV: Assessment Through Monte Carlo Code and Experimental Validation - Putro, G. E.; Omar, M. R.; Kasmudin, K.; Nuri, H. L.; Pancoko, M.; Jamil, A.; Subhiyah, H. (National Research and Innovation Agency, 2025)
Current plastic detectors need improvement in efficiency and accuracy, to enhance reliability. Simulation offers a cost-effective approach to accelerate detector development, yet its effectiveness relies on the reliability of the simulations used. Therefore, validating these simulations is crucial to ensure they accurately reflect actual scenarios and yield reliable results. This study employs the Monte Carlo approach to estimate the performance and efficiency of a plastic detector exposed to radiation sources within the 100–1300 keV energy range. The plastic detector (50 mm x 3 mm) was simulated using MCNP with Gaussian Energy Broadening (GEB) correction applied to capture detector response. Simulated data were then compared against experimental measurements to validate the model. This work aims to confirm that simulation results align with empirical data, ensuring theoretical models accurately represent physical phenomena. The study highlights both the limitations and strengths of simulation codes, leading to more efficient research through validated models. Notably, an 8.04 % deviation was observed at 662 keV for 137Cs, demonstrating a strong correlation between simulated and experimental results and confirming the model’s accuracy and reliability.